Theories in and of Mathematics Education - Bikner-Ahsbahs, Angelika; Vohns, Andreas; Schmitt, Oliver; Bruder, Regina; Dörfler, Willi (Cham Springer Nature, 2016)
Mathematics Education; Learning; Teaching
English
Keywords: Education; Mathematics & science; Mathematics Education; Learning; Teaching